Improvement of Inverted OPV Performance by Enhancement of ZnO Layer Properties as an Electron Transfer Layer1. (2016) - Polyzoidis, C.A.; Kapnopoulos, C.; Mekeridis, E.D.; Tzounis, L.; Tsimikli, S.; Gravalidis, C.; Laskarakis, A.; Logothetidis, S.
Abstract: In the present study we focus on the optimization of NP concentration of ZnO used as an ETL for the fabrication of fully printed inverted OPVs by lab-scale Sheet-to-Sheet gravure technique. The inverted OPV architecture consistσ of the layer sequence: PET/ITO/ZnO/P3HT:PCBM/PEDOT:PSS/Ag. By diversifying ZnO nanoparticle concentration, we track the optimum concentration for better OPV efficiencies and try to correlate concentration to the electrical characteristics of the OPV and other ETL characteristics such as thickness, surface morphology and roughness, hydrophilicity etc. Further goal of this work is to achieve a cost-efficient scalability of flexible organic photovoltaics (OPVs), the optimization of the ZnO NPs and of the printing processes.